2006
DOI: 10.1007/s00125-006-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of fasting glucose levels in a young genetically isolated population

Abstract: Aims/hypothesis: The heritability of fasting glucose levels in Northern European populations has been examined previously in twins and samples of small pedigrees. In this study the heritability of fasting plasma glucose (FPG) was estimated in participants in the Erasmus Rucphen Family study, who were members of a single pedigree from a young genetic isolate. We also studied the relationship between FPG and components of the metabolic syndrome. Methods: FPG, lipid, blood pressure and body composition measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…The genetic make-up of genetically isolated populations may differ from a general population as a result of genetic drift and founder effects. Even though our population is a genetic isolate we found no evidence that it deviates much from the general population in its genetic composition [23,34]. However, as was pointed out again recently [35], heritability estimates are by definition population-specific and replication of our findings in other populations is necessary.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The genetic make-up of genetically isolated populations may differ from a general population as a result of genetic drift and founder effects. Even though our population is a genetic isolate we found no evidence that it deviates much from the general population in its genetic composition [23,34]. However, as was pointed out again recently [35], heritability estimates are by definition population-specific and replication of our findings in other populations is necessary.…”
Section: Discussionsupporting
confidence: 44%
“…The aim of this programme is to identify genetic risk factors in the development of complex disorders [21][22][23]. Genealogical records demonstrated that almost all of the inhabitants of this isolated population could be traced back to about 150 individuals who founded this community about the year 1750.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated genetic influence for familial clustering of features of the metabolic syndrome. 34,35 Whether familial aggregation in our study is because of shared environmental and/or genetic factors cannot be concluded. Nonetheless, our data suggest a potential role for the glucose metabolism in the pathogenesis of both pregnancy disorders.…”
Section: Discussionmentioning
confidence: 77%
“…There was a high level of intra-pair agreement on contact frequency for the 4317 pairs in which both twins responded (rho = 0.81). The average level of contact frequency within the pair was used for (Fenger et al, 2007) e (Goode et al,2007) f (Henneman et al, 2008) g (Isaacs et al, 2007) h (McQueen et al, 2003) i (Snieder et al, 1999) j (Souren et al, 2007) k (VelasquezMelendez et al, 2007) l (Chien et al, 2007) m (Iliadou et al,2005) n (Hokanson et al, 2003) o (Beekman et al, 2002) p (Iliadou et al, 2001) q (Middelberg et al, 2002) r (Santos et al, 2006) s (Snieder et al, 2001) t (Simonis-Bik et al, 2008) u (Berrahmoune et al, 2007) v (Fox et al, 2008) w (Lange et al, 2006) x (Su et al, 2008) y (Wessel et al, 2007) z (Worns et al, 2006) https://www. these pairs.…”
Section: Twin Contact and Age At Separationmentioning
confidence: 99%